2022
DOI: 10.3390/v14081685
|View full text |Cite
|
Sign up to set email alerts
|

Serological Investigation and Genetic Characteristics of Pseudorabies Virus between 2019 and 2021 in Henan Province of China

Abstract: In late 2011, severe pseudorabies (PR) outbreaks occurred among swine herds vaccinated with the Bartha-K61 vaccine in many provinces of China, causing enormous economic losses for the pork industry. To understand the epidemic profile and genetic characteristics of the pseudorabies virus (PRV), a total of 35,796 serum samples were collected from 1090 pig farms of different breeding scales between 2019 and 2021 in the Henan province where swine had been immunized with the Bartha-K61 vaccine, and PRV glycoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
1
6
2
Order By: Relevance
“…From 2012 to 2017, the PRV strains circulating in China showed a significantly different evolutionary relationship compared to those in other countries [ 42 ]. From 2017 to 2021, varying degrees of PRV infections were found at pig farms in several provinces in China, with the presence of classical strains, variant strains, and recombinant strains [ 43 , 44 , 45 ]. These results demonstrated that existing commercial vaccines could not prevent the emergence of new strains of PRV.…”
Section: Discussionmentioning
confidence: 99%
“…From 2012 to 2017, the PRV strains circulating in China showed a significantly different evolutionary relationship compared to those in other countries [ 42 ]. From 2017 to 2021, varying degrees of PRV infections were found at pig farms in several provinces in China, with the presence of classical strains, variant strains, and recombinant strains [ 43 , 44 , 45 ]. These results demonstrated that existing commercial vaccines could not prevent the emergence of new strains of PRV.…”
Section: Discussionmentioning
confidence: 99%
“…Developed countries, such as the United States, utilize the gE gene deletion vaccine and accompanying diagnostic methods to control and eradicate PRV infections. However, PRV infections remain prevalent in swine herds with sporadic epidemics in many countries, including China [ 16 , 17 ]. In this study, the average positivity rate of PRV-gE was 29.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Liu et al found a decreased positive rate of PRV gE antibody from 2013 to 2016 (22.17% to 13.14%) ( 18 ). Chen et al analyzed 35,796 serum samples collected in Henan province from 2019 to 2021 and observed that the positivity rate of PRV gE antibody dropped from 25% to 16.69% ( 23 ). These epidemiological findings are consistent with our model results.…”
Section: Discussionmentioning
confidence: 99%